The Effectiveness of Vocabulary Self-Collection Strategy (VSS) Towards Students’ Vocabulary Enhancement - Nelson Balisar Panjaitan, Rosita Sihotang, (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2018)
The purpose of this study is to find student’s vocabulary enhancement using VSS strategy. This study used quantitative research method and experimental design. The sample of the study was the students of SMAN 1 Parongpong, Bandung in academic year 2016/2017. There were two classes in ten grades which were divided into the VSS group and conventional group with a total of 74 students. The result of this research was: normalized gain of VSS group is 0.423 while the group not taught by VSS is 0.385. And the data from T-Test found that the p-value Sig (tailed).(0.850)â‰¥Î±(0.05). It means that Ho is accepted, Ha is rejected. Based on the result of the data there is no difference in student’s vocabulary enhancement between students who were taught using VSS group and students who were taught using conventional group. Keywords: Vocabulary Self-collection Strategy